Molecular Defects in Friedreich’s Ataxia: Convergence of Oxidative Stress and Cytoskeletal Abnormalities - Smith, Frances M.; Kosman, Daniel J. (Frontiers in Molecular Biosciences, 2020)
Friedreich’s Ataxia (FRDA) is a multi-faceted disease characterized by progressive sensory-motor loss, neurodegeneration, brain iron accumulation, and eventual death by hypertrophic cardiomyopathy. FRDA follows loss of frataxin (FXN), a mitochondrial chaperone protein required for incorporation of iron into iron-sulfur cluster and heme precursors. Following the discovery of the molecular basis of FRDA in 1996, over two decades of research have been dedicated to understanding the temporal manifestations of disease both at the whole-body and molecular level. Early research indicated strong cellular iron dysregulation in both human and yeast models followed by onset of oxidative stress. Since then, the pathophysiology due to dysregulation of intracellular iron chaperoning has become central in FRDA relative to antioxidant defense and run-down in energy metabolism. At the same time, limited consideration has been given to changes in cytoskeletal organization, which was one of the first molecular defects noted. These alterations include both post-translational oxidative glutathionylation of actin monomers and differential DNA processing of a cytoskeletal regulator PIP5K1β. Currently unknown in respect to FRDA but well understood in the context of FXN-deficient cell physiology is the resulting impact on the cytoskeleton; this disassembly of actin filaments has a particularly profound effect on cell-cell junctions characteristic of barrier cells. With respect to a neurodegenerative disorder such as FRDA, this cytoskeletal and tight junction breakdown in the brain microvascular endothelial cells of the blood-brain barrier is likely a component of disease etiology. This review serves to outline a brief history of this research and hones in on pathway dysregulation downstream of iron-related pathology in FRDA related to actin dynamics. The review presented here was not written with the intent of being exhaustive, but to instead urge the reader to consider the essentiality of the cytoskeleton and appreciate the limited knowledge on FRDA-related cytoskeletal dysfunction as a result of oxidative stress. The review examines previous hypotheses of neurodegeneration with brain iron accumulation (NBIA) in FRDA with a specific biochemical focus.